Comparison of continuous with single-injection regional analgesia on patient experience after ambulatory orthopaedic surgery: a randomised multicentre trial. (September 2022) - Maurice-Szamburski, Axel; Grillo, Philippe; Cuvillon, Philippe; Gazeau, Thierry; Delaunay, Laurent; Auquier, Pascal; Bringuier, Sophie; Capdevila, Xavier
Abstract: Background: The optimal approach to improving patient experience and analgesia after ambulatory orthopaedic surgery remains unclear. Methods: This multicentre, randomised clinical trial compared single-injection nerve block analgesia with home delivery of continuous nerve block analgesia by remote-controlled electronic pump. The primary outcome was patient-reported satisfaction (Evaluation du Vecu de l'Anesthesie Generale [EVAN-G]; 0–100) assessed on postoperative Day 2. Secondary outcomes focused on pain, opioid consumption, quality of rehabilitation, activity tracking using a wearable electronic device, and 90-day quality of life. Results: We randomly assigned 294 patients to continuous pump delivery or single injection. For subjects with normal level of pain catastrophising (Pain Catastrophizing Scale <30; n =211), median global EVAN-G was higher with the electronic pump compared with the single injection (78 [69–86] vs 72 [63–84]; P =0.03), as were pain satisfaction scores ( P =0.01). For the maximum pain levels, the numerical rating scale score was 2.0 (1.0–5.0) in the electronic-pump group vs 5.0 (3.0–7.0) in the single-injection group on the first 2 days after surgery ( P <0.0001). Total opioid consumption in morphine equivalent was higher with single injection (mean [standard deviation]): 70.5 [73.8] vs 31.9 [54.2] mg; P <0.01). The groups did not differ in early rehabilitation on Day 1 or quality of life on Day 45. Electronic activity tracking indicated higher activity in the electronic-pump group ( P <0.01). Conclusions: Self-reported patient satisfaction at home was better with continuous nerve block analgesia via electronic pump vs single injection, without impairing early rehabilitation. Single-injection analgesia was associated with higher pain levels and opioid consumption and lower satisfaction. Patient catastrophising negatively affected the experience of pain. Clinical trial registration: NCT 02720965 .